Creating ‘classical’ Greek: from fourth-century practice to Atticist theory - Willi, Andreas (Rivista di Filologia e di Istruzione Classica, 2014)
Abstract Although it is widely used, the notion of ‘classical’ Greek is not easily defined with precision, since sociolectal, dialectal, and chronological criteria interact in its specification. At first sight, one might hold the Atticist grammarians of the first centuries AD responsible for the ‘classicisation’ of the particular variety of Greek thus labelled. In reality, however, all the Atticists did was codify a development that had begun much earlier, during the initial decades of the fourth century BC, when non-Athenian authors first chose to write in contemporary Attic. Whereas ‘classical’ Greek had thus been synchronically (horizontally) opposed to ‘non-classical’ Greek at the outset, this opposition turned into a diachronic (vertical) one over time; but the selection of the target variety itself remained unaffected by this change in perspective.